Low cost perennial water harvesting technology (Jalkund): A boon for farmers doubling income in the mild hill slopes - OINAM, GUNAJIT; SALAM, M. A. (Journal of Soil and Water Conservation, 2019)
The North Eastern Hilly (NEH) region of India is characterized by varying topology that is largely affected by high seepage flow and flash runoff. Dual effect of water in the form of heavy rainfall during monsoon and water scarcity during post monsoon is severe in this region. Existing undulated terrain and dual effects of water are the main limiting constrain in storing/ concentration of runoff water and its later use for irrigation purposes in NEH region. The main problem with the small land holdings along the mild hill slopes were due to presence of more undulated areas and unavailability of site for bigger pond construction for taking up farming activities by harvesting the water during the monsoon season. Many perennial springs which could provide water year round located above 150-200 m above the human inhabited area were identified and utilized to trap the water for taking up different farming activities and also for household consumption in the localities. A low cost perennial water harvesting technology called Jalkund of size 5m x 4m x 1.5m having 30000 liter water capacity has been developed in the mild hill slopes at farmer’s field of Imphal East District, Manipur. The cost incurred for construction of the structure was estimated to Rs. 6312/-. The harvested water were utilized for growing vegetable crops (Kharif and Rabi seasons) and rearing of poultry, Piggery and fisheries which act as a primary source of income for the farmers inhabited in mild hill slopes of the district. Using stored water economically in various farm activities is the most acceptable and profitable one particularly to those in the mild hill slopes, who are the worst suffering due to water scarcity. This economically viable and easily adoptable low cost technology needs to be popularized among the large section of farmers for doubling their income.